Normative political economy : subjective freedom, the market, and the state - Levine, David P., 1948- (Routledge, 2000)
Normative Political Economy explores the criteria we use for judging economic institutions and economic policy. It argues that prevailing criteria lack sufficient depth in their understanding of subjective experience. David Levine's arguments cover topics which include: * basic needs, equality and justice * freedom, self-integration and creative living * the role of the state * capitalism and the good society